2011
DOI: 10.1128/jvi.02403-10
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Drift in H5N1 Avian Influenza Virus in Poultry Is Driven by Mutations in Major Antigenic Sites of the Hemagglutinin Molecule Analogous to Those for Human Influenza Virus

Abstract: H5N1 highly pathogenic avian influenza virus has been endemic in poultry in Egypt since 2008, notwithstanding the implementation of mass vaccination and culling of infected birds. Extensive circulation of the virus has resulted in a progressive genetic evolution and an antigenic drift. In poultry, the occurrence of antigenic drift in avian influenza viruses is less well documented and the mechanisms remain to be clarified. To test the hypothesis that H5N1 antigenic drift is driven by mechanisms similar to type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 37 publications
7
86
0
Order By: Relevance
“…4). Eight amino acid differences were observed at sites known to be important for antigenic recognition (41)(42)(43)(44)(45)(46)(47)(48), including sites near the receptor binding site, and as previously reported (48), one potential glycosylation site whose sequence differed among the vaccine and challenge viruses was identified (Table 4). Three of the amino acids were specific to the Indonesian isolates (amino acid residues 124, 189, and 212).…”
Section: Methodsmentioning
confidence: 48%
“…4). Eight amino acid differences were observed at sites known to be important for antigenic recognition (41)(42)(43)(44)(45)(46)(47)(48), including sites near the receptor binding site, and as previously reported (48), one potential glycosylation site whose sequence differed among the vaccine and challenge viruses was identified (Table 4). Three of the amino acids were specific to the Indonesian isolates (amino acid residues 124, 189, and 212).…”
Section: Methodsmentioning
confidence: 48%
“…Indeed, many field studies have attributed the failure of vaccination to prevent infection and transmission of HPAI strains to-among other things-antigenic distances between the vaccine and the circulating field strains, and called for constant vaccine updating, the way it is done for human influenza vaccines [6,7,14,20]. These studies show that use of vaccines that are antigenically distant to the circulating strains led to lack of protection due to low HI titres against the challenge strains.…”
Section: Discussionmentioning
confidence: 99%
“…Results from countries where vaccination is in place show that if the vaccine coverage and the HI titres of vaccinated animals are high, then vaccination leads to a substantial decrease in transmissibility and infection of animals [17,34,43,53,54]. More studies emerging from the field show that ineffective vaccination has often led to selection of antigenic variants, which spread rapidly because there is in effect no protective immunity [4,5,7,8,14,15,17,55]. We argue that instead of this evidence making a case against vaccination it should provide even more reasons for vaccination to be applied in such a way that high HI titres against the challenge strains can be obtained, since if it is, a sufficient level of herd immunity can be achieved irrespective of the antigenic distance between vaccine and challenge strains that may result from initial selection in vaccinated chickens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clade B viruses circulating in poultry where vaccination has been used extensively had a much higher evolutionary rate compared with clade A. Interestingly, the genetic evolutionary rate of all H5N1 viruses in Egypt showed a sharp increase 1.5 years after the start of poultry vaccination programs, and sequence analysis showed that changes occurred primarily at predicted antigenic sites [5]. A comparison of H5N1 evolutionary rates found significantly higher rates in vaccinating than in nonvaccinating countries.…”
mentioning
confidence: 99%